Thromboelastogram and coagulation function index: relevance for female breast cancer - Peng, Qiongle; Zhu, Jinmei; Ren, Xiaoling (Frontiers in Oncology, 2024)
Thromboelastogram (TEG), platelet routine test (PLT), and coagulation function indicators for different breast disease patients were detected and analyzed to explore the predictive assessment of secondary bleeding. One hundred and thirty-one patients with breast diseases, admitted to Jiangsu University Affiliated Hospital from January 2019 to December 2022, were selected as the research subjects. We analyzed the aforementioned detection items using the receiver operating curve (ROC) after grouping for the secondary bleeding disease of breast cancer patients. The reaction time (R) and coagulation time (K) were lower in the malignant breast disease group, while coagulation rate angle (α), maximum amplitude (MA), coagulation index (CI), fibrinogen (FIB), and D-dimer (D-D) were higher than those in the benign breast disease group. The t-tests approved that MA and FIB values were statistically significant (p<0.05) in the benign and malignant breast disease group. The values of R and K of breast disease patients were positively correlated with activated partial thromboplastin time (aPTT), and D-D, and negatively correlated with PLT. The α-angle was negatively correlated with APTT and D-D but positively correlated with PLT. The MA for the platelet function was positively correlated with FIB and PLT. CI was negatively correlated with aPTT, thrombin time (TT), D-D, and positively correlated with PLT. ROC curve analysis showed that CI and α-angle had a significant predictive value, whereas the correlation of other indicators was relatively low. Coagulation tests show significant differences in patients with breast cancer, differing from those with benign breast disease. Thromboelastogram combined with conventional coagulation indicators is potentially valuable for predicting the secondary bleeding disease in breast cancer patients.